Systematic Literature Review: Penerapan model Project Based Learning dalam materi Teorema Pythagoras - Musri'ah, Isna; Aziz, Abdul; Sulistyaningsih, Dwi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to explore the implementation of the Project-Based Learning (PjBL) model in teaching the Pythagorean Theorem using the Systematic Literature Review (SLR) method. PjBL is an innovative, student-centered learning strategy that encourages collaboration in solving real-world problem-based projects. In the context of the Pythagorean Theorem, this model has been proven effective in enhancing students’ conceptual understanding, critical thinking skills, creativity, and problem-solving abilities. The data for this study were collected from 12 relevant articles published between 2021 and 2025, and analyzed based on their relevance and content quality. The review findings indicate that the use of PjBL—whether independently or integrated with learning media such as comics, pop-up books, and digital applications—can create a more meaningful and contextual learning environment while supporting the improvement of students’ mathematical literacy. Based on these findings, the study recommends that teachers implement the PjBL model in mathematics instruction to support the Merdeka Curriculum and encourage active student engagement in the learning process. Keyword: Project Based Learning, Pythagorean Theorem.